Learning from the web. - Bosworth, Adam (New York ACM, 2005)
The Web has taught us many lessons about distributed computing, but some of the most important ones have yet to fully take hold.
Keywords: General Literature; Miscellaneous; Information Systems; Models and Principles; Computing Methodologies; Document and Text Processing; Document preparation; Design; Human Factors